PUBLIC SERVICE QUALITY IN THE APPLICATION OF E-PBB AT THE REGIONAL REVENUE AGENCY (BAPENDA) SURABAYA - Putri, Rosalina Mega; Pramudiana, Ika Devy; Kamariyah, Sri; Sunarya, Aris (DIA: Jurnal Administrasi Publik, 2025)
This research examines the quality of public service in the application of E-PBB at the Regional Revenue Agency (BAPENDA) Surabaya, aiming to evaluate the effectiveness of the application in supporting ease, security, and citizen satisfaction in tax services. This study uses a qualitative method, collecting data through interviews and observations with E-PBB users and BAPENDA officers. Using Parasuraman’s ServQual model, the analysis focuses on five service quality dimensions. The results indicate that in terms of reliability, the E-PBB application achieved 85% but still requires improvements in information accuracy and processing speed. In the assurance dimension, the application shows an 80% success rate but needs better information on security systems and more responsive technical support services. Regarding tangibles, the application achieved 75% and requires interface design improvements to make it more accessible and understandable for users. Additionally, empathy scored 70%, where users expect more friendly and informative direct support when facing technical difficulties. For responsiveness, the E-PBB application reached 78%, though there is a need to improve response speed to user inquiries and complaints. Based on these findings, several recommendations are proposed to improve the quality of the E-PBB application service, including a user education program, strengthening technological infrastructure, and enhancing data security protocols. An intensive user education program and easier access to help centers will assist users in understanding and operating the application independently. Investing in a more robust server system and regular maintenance will ensure the application operates steadily, especially during peak usage times. Additionally, strict security protocols such as data encryption and cybersecurity threat monitoring will provide users with a sense of security. These recommendations are expected to improve the public service quality provided through the E-PBB application, strengthen public trust, and enhance user satisfaction in fulfilling their tax obligations online.